(untitled) - Franck, Thomas M. (Cambridge UK, 2002)
The United Nations Charter in 1945 prohibits all use of force by states except in the event of an armed attack or when authorized by the Security Council. Although the Charter is very hard to amend, its drafters agreed that it should be interpreted flexibly by the UN's principal political institutions and the text has undergone extensive interpretation. This book relates these changes in law and practice to changing public values pertaining to the balance between maintaining peace and promoting justice.
Keywords: Intervention (International law),Sự can thiệp (Luật quốc tế),Self-defense (International law),Tự vệ (Luật quốc tế)